POLA KOMUNIKASI ANTAR PENGGEMAR “iKON" SEBAGAI “CYBERFANDOM” DI TWITTER - Widayani, Ni Luh Ari; Purnawan, Ni Luh Ramaswati Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
ABSTRACT This study aims to determine the communication pattern applied by iKONIC as a cyberfandom on Twitter. This research is descriptive qualitative research by applying the netnography method. The selection of informants is based on the availability and willingness of the informants. The research data were obtained through two sources. The primary sources of this research were through depth interviews and participant observations. The secondary sources come from previous works of literature related to this research. The data obtained from this research were analyzed through several stages, through data reduction, data presentation, conclusion, and verification. Through this research, it is known that iKONIC as a cyberfandom on Twitter generally applied all channels pattern on the communication process. In different context of interactions this fandom applies three different types of communication patterns based on the communication context, those types are Y pattern, wheel pattern and circle pattern. Keywords : Communication pattern, cyberfandom iKONIC, Twitter, netnography